Using Rhizhopora apiculata Extract for Mosquito Larvae Control - Soni Sanjaya; Irwan Effendi; Nursyirwani Nursyirwani (Tropical Marine Enviromental Sciences, 2022)
Temephos is the most commonly used synthetic larvicide to control vectors of several diseases. Currently in some areas there has been resistance of larvae to temephos, so natural larvicides are needed as an alternative. Rhizophora apiculata contains flavonoid compounds that are respiratory toxins to some larvae. This research was conducted in March - Juny 2022, to determine the inhibitory of mangrove extract against mosquito larvae in brackish water. Samples were collected from the Bakar Bakau Dumai, Riau Indonesia. The experiment was setted in a single factor experimental design. Mangrove leaves are finely ground and kneaded while mixed with water and deposited for 6 minutes and filtered. This extract solution was mixed with brackish water to obtain a test medium of 500 l with a concentration of 6 (a1), 9 (a2) and 12% (a3), positive control or 1 g of abate powder (a4) and negative control or brackish water (a0). A total of 20 mosquito larvae were put into the media and their mortality was observed at 0, 15, 30, 45 and 60 minutes after introduction. The mortality of larvae were then analyzed using probit analysis to obtain LC50 (Lethal Concentration 50) and LT50 (Lethal Time 50) values. R. apiculata extract is toxic to mosquito larvae, where larval death has been seen since 15 minutes and continues until 60 minutes after introduction. At the 60th minute the mortality rate is as follows; a1 (60 %), a2 (80 %), a3 (100 %), a4 (100 %), and a0 a1 ( %). Based on the results of the above probit values ​​in the LC50 and LT50 tests on R. apiculata leaves, the LC50 value is 9,732 while the LT50 value is estimated at 21,217